Implementation of Fun Learning Innovation To Improve Children's Spiritual Intelligence in Early Childhood Education (Paud) Indragiri Hilir Riau - Faridatul Faridatul; Zamsiswaya Zamsiswaya; Asmal May (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the implementation of Funlearning learning innovation in Early Childhood Education (PAUD) Indragiri Hilir, Riau, in order to improve children's spiritual intelligence. The concept of Funlearning is rooted in a fun, interactive, and creative learning approach, designed to support children's holistic development. In the context of PAUD, spiritual intelligence is an important aspect that includes moral values, introduction to the concept of divinity, and the formation of strong character in children. This study uses a qualitative method with a descriptive approach. Data collection was carried out through interviews, observations, and documentation of educators, children, and parents at PAUD Indragiri Hilir. The results of the study show that the Funlearning method can increase children's enthusiasm in the learning process, so that children can more easily understand and internalize spiritual values. The activities carried out include educational games, moral stories, singing, and creative arts designed to connect children with spiritual experiences naturally. Educators have a vital role in developing the curriculum, creating a conducive atmosphere, and facilitating children's interaction with the surrounding environment. In addition, the involvement of parents as supporters of home learning also strengthens the effectiveness of this program. The conclusion of this study emphasizes the importance of Funlearning learning innovation as a strategic approach to spiritually enlighten children from an early age. The practical implication of this study is the development of a more holistic and integrated learning model in PAUD, especially in terms of strengthening spiritual values. These findings recommend ongoing training for educators and increased collaboration between schools and families to support the implementation of effective and sustainable Funlearning.